Traffic-related pollution (NO2 and CO) and its association with asthma symptoms among 10-11 year old children in Malaysia - Zainal Abidin, Emilia (2012)
Introduction: Children attending schools located close to major traffic sources are exposed to higher indoor air pollution levels due to infiltration of outdoor air pollutants. This study investigates the respiratory health of Malaysian schoolchildren in relation to indoor air pollution in schools and at home.